The Impact of Recruitment Practices And Crew Turnover On Employee Performance, Mediated By Work Motivation, At PT Humpuss Maritim Internasional - Muhamad Akmal Firdaus; Zainul Kisman (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2026)
This research examines how recruitment practices and crew rotation influence ship crew performance, considering work motivation as an intervening factor at PT Humpuss Maritim Internasional. The study is motivated by observed inconsistencies in crew performance, skill mismatches in job assignments, and delays in crew replacement that potentially reduce motivation and overall effectiveness. A quantitative explanatory design was applied, with data gathered questionnaires from crew members and relevant departments. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Findings reveal that well-structured recruitment procedures positively contribute to both employee motivation and performance outcomes. Similarly, the management of crew rotation significantly affects these variables, either directly or through indirect pathways. Work motivation is confirmed as a key mediating variable that enhances the relationship between recruitment quality, crew turnover, and performance levels. These results highlight the importance of aligning recruitment strategies with job requirements and ensuring timely and well-managed crew transitions. From a practical standpoint, the study recommends that organizations improve recruitment standards and optimize crew scheduling systems to maintain operational efficiency and ensure safety in maritime operations.